2017
DOI: 10.1016/j.jaci.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Skin microbiome promotes mast cell maturation by triggering stem cell factor production in keratinocytes

Abstract: Background Mast cell (MC) progenitors leave the bone marrow, enter the circulation, and settle in the skin and other tissues. Their maturation in tissues is influenced by the surrounding microenvironment. Objective We tested the hypothesis that environmental factors play a role in MC maturation in the skin. Methods MCs were numerically, phenotypically, and functionally compared between germ-free (GF), SPF, and GF mice reconstituted with microbiota. Maturity of MCs was then correlated with skin levels of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 43 publications
5
107
0
Order By: Relevance
“…Moreover, the ability of immature Kit W‐sh/W‐sh MCs to differentiate in vitro when co‐cultured with Fb showed that albeit SCF is fundamental, SCF‐independent pathways might exist for MC maturation in the skin. Notably, the local skin microbiota was found to be crucial for MC maturation; indeed lipoteichoic acid (LTA) produced by Staphylococcus aureus can trigger the production of SCF in keratinocytes found in close proximity of MCs . In fact, germ‐free mice display higher numbers of immature MCs, characterized by positive staining for chymase and toluidine blue but negative for c‐Kit and FcεRI, that increase their expression of c‐kit only after re‐establishment of the normal microbiome.…”
Section: Mast Cells and Skinmentioning
confidence: 73%
“…Moreover, the ability of immature Kit W‐sh/W‐sh MCs to differentiate in vitro when co‐cultured with Fb showed that albeit SCF is fundamental, SCF‐independent pathways might exist for MC maturation in the skin. Notably, the local skin microbiota was found to be crucial for MC maturation; indeed lipoteichoic acid (LTA) produced by Staphylococcus aureus can trigger the production of SCF in keratinocytes found in close proximity of MCs . In fact, germ‐free mice display higher numbers of immature MCs, characterized by positive staining for chymase and toluidine blue but negative for c‐Kit and FcεRI, that increase their expression of c‐kit only after re‐establishment of the normal microbiome.…”
Section: Mast Cells and Skinmentioning
confidence: 73%
“…LTA makes the cells more resistant to UVB. The SE which we used in our experiments is the <10‐kDa fraction from S. epidermidis culture supernatant and contains very low quantities of LTA; therefore, it loses the added advantage that comes from containing large quantities of LTA. PA supernatant, the <10‐kDa fraction from P. acnes , does not prevent, but strongly increases melanocyte apoptosis after UVB irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, our skin is also covered by the microbiome which has been proven to have a very important role in different skin diseases, such as atopic dermatitis, acne, and psoriasis . Specific skin commensal bacteria, such as Staphylococcus epidermidis (S. epidermidis) and its product LTA (lipoteichoic acid, also known as a TLR2 ligand), have been implicated in immune modulation by affecting the recruitment and function of various immune cells such as mast cells . In addition, LTA produced by staphylococcal species have a unique anti‐inflammatory action on keratinocytes .…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about whether or how the skin microbiome modulates the differentiation, survival, and function of MCs. Our group has recently published that the skin microbiome influences MC maturation in the dermis and that a normal microbiome is necessary for correct function and maturation of MCs [83]. In fact, in GF mice, MCs present lower expressions of the c-Kit and IgE receptors (Figure 3).…”
Section: The Microbiome Influencementioning
confidence: 99%
“…Moreover, upon co-housing GF mice with specific pathogen-free (SPF) mice, GF mice regained their microbiome and converted back to a normal MC phenotype. Furthermore, when GF mice were stimulated in vivo with compound 48/80 injections in the skin, the resulting inflammation was much lower than in the SPF mice, suggesting altered MC function [83]. This discovery is of fundamental importance for a better understanding of the genesis of skin diseases like AD in which changes in the skin microbiome have been considered to be responsible for eczema flares.…”
Section: The Microbiome Influencementioning
confidence: 99%